Finding The Maqashid Al-Syariah Performance Model on Syariah Management Accounting Information System Values - Baining, Mellya Embun; Hizazi, Achmad; Arum, Enggar Diah Puspa; Amir, Amri (Al-Risalah, 2024)
In Indonesia’s Zakat Management Organisation (OPZ) context, managing zakat funds effectively and in line with maqasid al-syariah principles is crucial to maintaining public trust. This study investigates the impact of environmental uncertainty, human resource (HR) competence, internal control, and Islamic organizational culture on the values of the Sharia Management Accounting Information System (SIAMSy) and the performance of zakat management organizations (KOPZ), as well as examining the role of information technology as a moderating factor. Primary data were collected through questionnaires and interviews with zakat management organizations (OPZ) in Jambi Province and analyzed quantitatively. The data analysis technique used is Structural Equation Modeling (SEM) with a Partial Least Squares approach. (PLS). The direct testing results show that HR competency and Islamic organizational culture significantly influence SIAMSy values. On the contrary, environmental uncertainty and internal control do not substantially impact enhancing SIAMSy values. Meanwhile, KOPZ is directly influenced by ecological uncertainty and internal control, while human resource competence and Islamic organizational culture do not significantly affect KOPZ. The indirect testing results explain that human resource competence and Islamic organizational culture have a positive and significant impact on KOPZ through SIAMSy with complete mediation, indicating that the role of SIAMSy values is found in KOPZ from the maqashid al-syariah perspective. Meanwhile, environmental uncertainty and internal control do not positively and significantly impact KOPZ through SIAMSy values in OPZ in Jambi Province. Lastly, information technology cannot provide a moderating effect between variables.